Assessing oxygen saturation in retinal vessels in high myopia patients pre‐ and post‐implantable collamer lens implantation surgery. Issue 6 (15th February 2017) - Chen, Pei; Cai, Xiaoxiao; Xu, Lijun; Zhang, Jing; Yang, Ying; Gao, Qianying; Ge, Jian; Yu, Keming; Zhuang, Jing
Abstract: Purpose: To determine whether posterior chamber phakic implantable collamer lens (ICL) surgery in high myopia patients impedes oxygen saturation of retinal vessels. Methods: Mean oxygen saturation and diameter in retinal blood vessels were measured before and after ICL implantation surgery to correct high myopia refractive errors (i.e. −6.00 to −20.25 dioptres [D]), using an Oxymap T1 retinal oximeter. Results: In 17 eyes of 17 patients, the Oxymap T1 retinal oximeter detected a small but significant decrease in oxygen saturation of retinal venules, 1‐week postoperatively (compared to preoperative measurements). Moreover, at 1 week after ICL implantation, the diameter of patient retinal vessels had consistently contracted, compared to preoperative measurements. By 1 month after ICL surgery, however, both the oxygen saturation and retinal vessel diameter had returned to preoperative levels. Otherwise, no statistically significant difference in oxygen saturation and diameter of retinal arterioles was found when comparing their measurements before and 1 week after implantation. Conclusion: Stable levels of oxygen saturation in retinal vessels, as detected by the Oxymap T1 oximeter, show ICL implantation would not leave lasting impact or adverse effects to retina oxygen saturation in high myopia patients.